The non-judicial divorces in the European Union and its impact on European Regulations - Jiménez Blanco, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The progressive appearance of non-judicial divorces in the EU has a direct impact on European Family Regulations. In particular, Regulation (EU) No. 2019/1111 regulates, for the first time, the recognition of registered private agreements, equating it in its treatment to judicial resolutions. With this, recognition is simplified, but doubts are raised regarding the application of the rules of jurisdiction and regarding the applicable law. It is necessary to prevent divorce tourism and ensure control over consent. At the same time, the problems of coordination with the rest of the Regulations are examined, in relation to the effectiveness with respect to parental responsibility, maintenance obligations or the matrimonial economic regime. The risk will come from cross-border divorces only partially effective.